Influence of Service Quality on Customer Engagement with Customer Emotions as an Intervening Variable in Aman Cepat Company - Susanto, Veronica Puspitasari; Herdinata, Christian (Review of Management and Entrepreneurship, 2022)
Aman Cepat is a family business that runs in the shipping service sector. Aman Cepat has problems in sales which have not reached the sales target. Moreover, Aman Cepat has customer complaints regarding its ser- vice quality dimensions (personnel, outcome, and social quality), and cur- rently, competition in the expedition service sector is getting tougher. This research aims to test and analyze the influence of service quality dimen- sions towards customer emotions and the effect of customer emotions on customer engagement of Aman Cepat. The benefit of this research is that it is expected that the Aman Cepat Company can provide better quality in service. This research has novelty in the field of the industry being studied. The population of this research is the active B2B customer of the company, and the samples are 78 respondents, who were chosen using the saturated sampling method. This research uses the Partial Least Square Structural Equation Modelling. The results show those service quality dimensions have a significant influence on customer emotions, and the customer emotions variable also has a considerable influence on the customer engagement of Aman Cepat.